KEANEKARAGAMAN DAN POLA DISTRIBUSI (Tridacnidae) PADA WILAYAH PASANG SURUT DESA HERLEY KABUPATEN MALUKU BARAT DAYA - Stevin Melay; Hasan Tuaputty; Herman Jotlely (Science Map Journal, 2020)
Herley is one of the coastal coastal areas that has a very large biodiversity, this region has a fairly wide landscape and is a rocky, rocky and sandy beach that has become a living place for various types of marine biota such as algae (seaweed), bivalves, tridacnidae , growing coral reef fish and various other invertebrate organisms. In addition, the herley area is also a residential area and from year to year the herley community performs various types of activities such as taking marine rocks as a house building and growing coral used as lime fire building materials so that the type of marine biota especially bivalvia tridacnidae is threatened with extinction This study was conducted in October until November 2018 aiming to determine the diversity and distribution patterns of tridacnidae in coastal waters. ey in length. 130 area of 13,000 so 5% of the area as the area for determining transects and sampling tridacnidae. Samples in the study were tridacnidae contained in the sampling area or observation plot measuring 1x1 meter in the coastal waters of herley village